A remark on very ample linear series: III - Martens, Gerriet (Archiv der Mathematik, 2019)
Let C be the general k-gonal curve. Our aim is the determination of its complete and very ample linear series for k= 4. Though the simple description obtained is no longer valid if k> 4 we still can prove related results for k= 5.
CRIS-Team Scopus Importer:2019-12-31
Keywords: 4-gonal curves; Linear series; Very ample